Legal Policy Applications for Enhancing the Quality of Public Administrative Services - Tran Thi Bich Nga (Emerging Science Journal)
Vietnam is now focused on market economic growth and administrative reform. This involves organizing and administering society via legal institutions and meeting the fundamental requirements of the people by providing public administrative services. In addition, the execution of public administrative services is a vital and indispensable responsibility for government agencies, as well as for the citizens. Hence, the objective of the research is to investigate the primary factors that influence the public administration service quality in Ho Chi Minh City, Vietnam. The author employed both qualitative and quantitative methodologies to examine data obtained from a survey sample of 900 individuals. The study focused on assessing the public administration service quality in nine districts of Ho Chi Minh City, Vietnam. In addition, the study included descriptive statistical techniques such as calculating the mean and standard deviation. Furthermore, it utilized structural equation modeling with the assistance of SPSS 20.0 and Amos software. The article identifies eight crucial factors that influence the public administrative service quality and have an impact on people's satisfaction with these services. The primary factors clearly list the factors analyzed, such as reliability, empathy, responsiveness, competence, tangibles, legal regulations and policies, technology application, and management capacity. The study's originality enables policymakers and public service managers to utilize the findings in order to improve the public administration service quality and boost people's satisfaction. There are several suggested legal policy applications aimed at achieving equal quality in public administrative services. These policy recommendations prioritize investment in technology applications, improving management capacity, and updating legal regulations and policies to increase awareness across society and create favorable conditions for businesses and individuals. This novelty will facilitate the implementation of administrative procedures through online public services to develop e-government.